Leverage and Corporate Financial Distress in Nigeria: A Panel Data Analysis - Lucky, Lucky Anyike; Michael, Agilebu Ogechi (Asian Finance & Banking Review, 2019)
This study examined the effect leverage on corporate financial distress of quoted manufacturing firms in Nigeria. The objective is to examine if financial leverage have any effect on financial distress of the Nigeria firms. Cross sectional data was sourced from financial statement of ten quoted manufacturing firms. Z-Score and Changes in operating profits was proxy for corporate financial distress while debt equity ratio, short, long term debt and total debt to total assets were proxy for leverage. After cross examination of the validity of the pooled effect, fixed effect and the random effect, the study accepts the fixed effect model.  Findings reveal that financial leverage have positive effect on financial distress measured by the z-score while total debt ratio and debt equity ratio have positive effect on financial distress measured by changes on operating profits while  short term debt and long term debt have negative effect on operating profits. From the regression summary, the study concludes that leverage have significant effect on corporate financial distress. We recommend that Financial structure of the manufacturing firms ought to be adequately planned to safeguard the interest of the equity holders, shareholders and financial requirements of the firm and the firms should formulate policies of increasing its equity capital as oppose to debt and that Implementable investment policies should be formulated and the business environment should be well examined. Recognizing faults of investment might be paramount to develop the business’s financial performance, since it specifies the loopholes which corrective decision can be applied.